Is the unbound concentration of atazanavir of interest in therapeutic drug monitoring?. (25th October 2016) - Metsu, David; Seraissol, Patrick; Delobel, Pierre; Cinq‐Frais, Christel; Cuzin, Lise; Izopet, Jacques; Chatelut, Etienne; Gandia, Peggy
Abstract: To date, therapeutic drug monitoring (TDM) is carried out with antiretrovirals and is usually based on total concentrations ( C t ). However, for some patients, TDM does not reflect efficacy or the avoidance of toxicity as is the case for atazanavir (ATV), a HIV protease inhibitor. As the unbound concentration ( C u ) is the pharmacological active form, the aim of the study was to evaluate the value of C u and the unbound fraction ( f u, f u = C u / C t ) for the TDM of ATV. The variability of C u and the corresponding f u of ATV was explored in 43 patients treated with ATV for an average of 13.5 months. C u was determined by coupling ultrafiltration and liquid chromatography. As ATV is highly bound to alpha‐1 acid glycoprotein (AAG), the correlation between f u and AAG was also evaluated. The viral load was monitored to evaluate the patients' virologic response, while total plasma bilirubin and unconjugated plasma bilirubin were used as biomarkers of ATV toxicity. Median trough C u and C t were 37.9 μg/L (Interquartile range (IQR) 20.6–94.9 μg/L) and 628.6 μg/L (IQR 362.7–1078.1 μg/L), respectively. f u, C u and C t showed high variability, but the f u variability was not correlated with the AAG level. The unbound concentration and fraction were unrelated to the virologic response ( P = 0.21 and P = 0.65 for C u and f u, respectively) nor to the unconjugated bilirubin (Pearson correlation coefficient (ρ), ρ = 0.22; P = 0.17 for C u ). Neither total nor unbound concentrations of ATV fully explained hyperbilirubinaemia or virologic failure. From this study, we conclude that unbound ATV did not appear to be more relevant than C t .